Determinan Intensi Whistleblowing: Persepsi dukungan organisasi sebagai variabel moderasi - Septiana Dwi Lestari; Siti Mutmainah (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
Fraud is a global problem that affects all organizations around the world. The results of the ACFE Indonesia survey show that in Indonesia Fraud the most common Fraud is through the whistleblowing. There are several factors that influence someone to do whistleblowing. This study aims to prove the effect of attitudes, subjective norms, perceived behavioral control, and perceived authentic leadership on whistleblowing and to examine the role of perceived organizational support in moderating these interactions. The sample used is ASN in the Tegal District Government. This study uses purposive sampling for the selection of respondents. The type of data used in this study is primary data. Based on the questionnaire distribution process, the number of samples was 449 respondents. Furthermore, testing the hypothesis in this study using the software WarpPLS 7.0 The results show that attitudes, subjective norms and perceived authentic leadership have a positive effect on intention internal whistleblowing. Meanwhile, perceived behavioral control has no effect on intention internal whistleblowing. Perceived organizational support can weaken the influence of attitudes, perceived behavioral control and perceived authentic leadership on intention internal whistleblowing and cannot moderate subjetive norms of intention internal whistleblowing.